2008
DOI: 10.1080/16184740802461629
|View full text |Cite
|
Sign up to set email alerts
|

Networks and the Organization of Identity: The Case of Norwegian Snowboarding

Abstract: In this article a particular aspect of change in the organization of sport is addressed: Confederation of Sports (NOC). The paper demonstrates that networking activities may be used to create and sustain new social entities such as the NSBF. However, networks as organizational forms also create contradictions to traditional sport systems that need to be solved through bargaining, concealment or challenging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
8
0
2
Order By: Relevance
“…Chaskin (2001) and Glickman and Servon (1998) also found that partnerships were critical elements in in their capacity, because it enables access to shared resources, knowledge, and experience. Partnerships and network linkages have also been considered as important for local and community sport organizations in a number of studies (e.g., Babiak 2007;Ferrand and McCarthy 2008;MacLean et al 2011;Steen-Johnsen 2008). Misener and Doherty (2009) confirmed this importance in their study on capacity in a nonprofit community sports club.…”
Section: Organizational Capacity In Nonprofit and Sports Researchmentioning
confidence: 91%
“…Chaskin (2001) and Glickman and Servon (1998) also found that partnerships were critical elements in in their capacity, because it enables access to shared resources, knowledge, and experience. Partnerships and network linkages have also been considered as important for local and community sport organizations in a number of studies (e.g., Babiak 2007;Ferrand and McCarthy 2008;MacLean et al 2011;Steen-Johnsen 2008). Misener and Doherty (2009) confirmed this importance in their study on capacity in a nonprofit community sports club.…”
Section: Organizational Capacity In Nonprofit and Sports Researchmentioning
confidence: 91%
“…Most studies of organisational change in sports have suggested that, only in rare cases, have sport organisations (and no international federations) escaped isomorphic trends and demonstrated some variation in structures. For example, Flatum (2013, interviewee) and Steen-Johnsen (2008) referred to the example of the Norwegian Snowboard Federation (the NSBF) that won a battle to attain the status of an autonomous federation responsible for snowboarding in Norway, as the Norwegian Skiing Federation sought to incorporate the sport. Consequently, organisation of competitive snowboarding in Norway can be characterised by a "strong degree of interactivity in organizational processes, the informality and the preference for making decisions without the explicit use of authority" [Steen-Johnsen, (2008), p.347].…”
Section: Discussionmentioning
confidence: 99%
“…This concept is underpinned by the differentiation view of the culture of an organisational field, which suggests that organisations can fulfil multiple purposes and embody multiple logics (Kraatz and Block, 2008). The possibility of the coexistence of various institutional logics has emerged as a result of studies in sports by Fahlen (2006), , , and Steen-Johnsen (2008) and Skirstad and Chelladurai (2011).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…(Paulus Ähtävä, henkilökohtainen tiedonanto 16.11.2011) Ähtävän kommentin perusteella voisi päätellä, että valmennusta kaipaavat ja kilpailuihin tähtäävät nuoret saattavat olla seurojen ja liiton toiminnassa mukana, kun taas kuvauspuolta harrastavat ja lumilautailun sosiaalista puolta painottavat nuoret organisoivat toimintaansa kaveriporukoiden toimin. Suomen Lumilautaliitto joutuu toimintatavoissaan huomioimaan nämä lajin harrastajille ominaiset identiteetit, joihin lajiliittokin on harrastajia edustaessaan sidottu (Steen-Johnsen 2008). Suomen Lumilautaliitto onkin pyrkinyt pois pelkästä seuratoimintaleimasta tekemällä yhteistyötä esimerkiksi yksityisten kilpailujärjestäjien kanssa, jolloin liiton kilpailukiertueet on järjestetty harrastajien arvostamien yksityisten toimijoiden organisoimina.…”
Section: Lumilautailu Suomalaisen Organisoidun Toiminnan Kontekstissaunclassified